Análisis y propuesta de un manual de seguridad y salud ocupacional para la empresa “Distribuidora Oriental” en la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2016 - Granda Ruilova, Yesenia Judith (2017)
The present research work entitled "ANALYSIS AND PROPOSAL OF A MANUAL OF SAFETY AND OCCUPATIONAL HEALTH FOR THE COMPANY" EASTERN DISTRIBUIDOR "IN THE CITY OF NUEVA LOJA, CANTÓN LAGO AGRIO, PROVINCE OF SUCUMBÍOS, FOR THE YEAR 2016. Its general objective was to propose a Manual of Occupational Safety and Health for the company "Distribuidora Oriental", Canton Lago Agrio, whose main activity is to sell sausages, wholesale of processed meats, rice and preserves. The specific objectives of the following research are: to establish the General Occupational Health and Safety standards for the company, to make a diagnosis of Occupational Health and Safety requirements for the "Eastern Distributor", to provide the company with the evaluation and monitoring instruments of Occupational Health and Safety requirements and to draft the occupational health and safety manual. Also this work has had its full theoretical support that has served to reinforce the information we have obtained, the methods used were: analytical that served to analyze the documents and the information obtained in the reviews that tells us what are the risk factors and reduce them, inductive used in the observation sheets, deductive that helped determine the shortcomings that the company has in relation to occupational safety and health and the statistician that helps us with the corresponding geographical representations. Among the techniques used is the observation used in the visits and physical findings that were made to the company, the survey applied to the workers, the same that allows to analyze internally the company, the interview was made to the owner manager where the weaknesses and strengths of the company. A survey of 39 employees of the company was carried out. In addition, the Manager was interviewed. It was possible to know that, of the 40 employees of the company, 60% were aware of the measures implemented in the company to reduce occupational risks. 100% of workers are unaware of the importance of ergonomics within the workplace, especially in the administrative area, who because of bad work habits usually turn on a computer and are unaware of: correct back position, visual angles, direct light and indirect, carpal tunnel problems and so on. In the issue concerning drivers and traffic law, there is a 100% compliance to total satisfaction. The entire investigative process that has been used and reflected in the present work has allowed to collect, analyze, synthesize and present sufficient technical support that demonstrates the prevailing need to implement an occupational health and safety manual in the company "Distribuidora Oriental" with the sole purpose of safeguarding the physical, mental and social integrity of each of the employees of the company, establishing the respective conclusions and recommendations.